(untitled) (Nigerian Journal of Technology, 2009)
The sediment discharges into the Kubanni Reservoir (KR) has been measured and analysed in this study. The predominant sandy-clay sediment in the reservoir has an estimated total sediment load of 20,387,000 kg/year. The depth and area coverage of the reservoir was surveyed using a defined distributed grid line configuration. By simple comparative analysis, KR had lost 48% (1.26 H 106 m3) of its initial volume (2.6 H 106 m3) to sedimentation in 33 years of its operation. This implies that the reservoir had experienced severe stacking of sediments over the past years. Fluvial discharge measurements and analytical data required for planning and management of sediment deposition in KR have also been obtained